TOWARDS INTERCULTURAL COMPETENCE: MODELS AND FRAMEWORKS FOR DEVELOPING ESOL LEARNERS' INTERCULTURAL COMPETENCE IN IRELAND - Gyorgy Nagy (Informascope, 2018)
Without the study of culture, second language acquisition is not complete (Kramsch, 1993). Teaching about culture raises the learners' awareness of the target culture and compares it with the home culture, providing an intercultural competence (Ibid). Due to the growing number of immigrants in Ireland (CSO Ireland, 2017), there is also an increasing number of immigrant learners in the English for Speakers of Other Languages (ESOL) providers in Ireland. The successful integration of these learners into Irish society depends on the successful development of their intercultural competence. This paper aims to provide insight into the models and frameworks for developing intercultural competence through the use of English language teaching materials in an Irish context. The paper involves presenting four models-based frameworks. The frameworks consider increasing content knowledge, sharpening mental skills, fostering attitudinal skills and increasing awareness which constitute the four fundamental components of intercultural competence. The paper endeavours to contribute to the vibrant global conversation among professionals about how to develop intercultural competence. Most significantly, however, it attempts to support teachers in incorporating cultural elements into their teaching materials effectively and appropriately.